Associação entre qualidade de vida e polimorfismos no gene de transporte da serotonina (5HTT) em pacientes com deformidade dentofacial - Santos, Felipe Silvério dos (2017)
Introduction: Dentofacial deformities are skeletal discrepancies associated with malocclusion that may be associated with aesthetic and functional outcomes, as well as altered physical, psychological and social outcomes. The serotonin transport gene (5HTT) is located on chromosome 17 (q11.1-q12). Variations in the alleles of this gene are known to have a significant impact on the likelihood of developing psychosomatic disorders such as autism, depression and schizophrenia in addition to interfiring with personality traits related to anxiety. Objective: To investigate whether the quality of life of individuals with dentofacial deformity is associated with 5HTT. Materials and methods: The study sample consisted of 147 adult patients of both sexes with dentofacial deformity who were submited to orthognathic surgery. All patients were evaluated one week before orthognathic surgery, through the collection of clinical data, application of the OHIP-14 questionnaire and collection of saliva for DNA extraction. The serotonin (5HTT) transport gene was genotyped through the markers rs3812034 and rs1042173, using the real-time PCR technique. The data were submitted to statistical analysis with a level of significance of 0.05. Results: Women presented worse quality of life when compared to men (p = 0.027). Younger patients present worse perception of quality of life when compared to patients with higher age groups (p = 0.001). In addition, patients with limited oral opening also have a poorer quality of life (p = 0.001). It was observed that rs3813034, in the additive model, was associated with OHIP-14 (p = 0.05). Heterozygous (AC) patients presented worse quality of life when compared to homozygotes, and these individuals presented an increase of 5.26 units in OHIP-14 (p = 0.03), regardless of mouth opening and gender. In addition, it is possible to infer that with each millimeter of decrease of the buccal opening, there is an increase of 0.027 units of OHIP-14 (p = 0.02).